THE EFFECT OF CONSUMER BEHAVIOR ON PURCHASE DECISIONS AND PRODUCT QUALITY IN THE TANGERANG REGION (CASE STUDY: USING TELKOMSEL SIMPATI FLASH): THE EFFECT OF CONSUMER BEHAVIOR ON PURCHASE DECISIONS AND PRODUCT QUALITY IN THE TANGERANG REGION (CASE STUDY: USING TELKOMSEL SIMPATI FLASH) - Arthawati, Sri Ndaru (Management Science Research Journal, 2022)
The Indonesian Telecommunications Company (Persero) Tbk is a state-owned enterprise (BUMN) engaged in information and communication technology services and telecommunication networks in Indonesia, offering a variety of products offered by the Telkomsel Company to the public in Indonesia, including cellular cards (simcard) or so-called with the name Sympathy Flash. Simpati Flash supports its users to be able to access the internet via smartphones, even now almost all simcard products support accessibility with 4G networks which are considered to have the advantage of being able to access the internet relatively quickly so that consumers feel satisfied with the quality of the Simpati Flash product. The research method uses quantitative methods. This research is divided into two parts, namely descriptive design and causal design. Data collection techniques were carried out by distributing questionnaires with a sample of 100 respondents. Analysis of the data using statistical testing with SPSS version 20 statistical program. Based on the results of hypothesis testing, it is known that purchasing decisions and product quality Simpati Flash will affect consumer behavior Telkomsel Simpati.